Responsive Thalamic Neurostimulation: A Systematic Review of a Promising Approach for Refractory Epilepsy - Feigen, Chaim M.; Eskandar, Emad N. (Frontiers in Human Neuroscience, 2022)
Introduction: Responsive neurostimulation is an evolving therapeutic option for patients with treatment -refractory epilepsy. Open-loop, continuous stimulation of the anterior thalamic nuclei is the only approved modality, yet chronic stimulation rarely induces complete seizure remission and is associated with neuropsychiatric adverse effects. Accounts of off-label responsive stimulation in thalamic nuclei describe significant improvements in patients who have failed multiple drug regimens, vagal nerve stimulation and other invasive measures. This systematic review surveys the currently available data supporting the use of responsive thalamic neurostimulation in primary and secondary generalized, treatment-refractory epilepsy. Methods: A systematic review was performed using the following combination of keywords and controlled vocabulary: ("Seizures"[Mesh] AND 104 "Thalamus"[Mesh] AND "Deep Brain Stimulation "[Mesh]) OR (responsive neurostim* AND 105 (thalamus[MeSH])) OR (responsive neurostimulation AND thalamus AND (epilepsy OR 106 seizures)). In addition, a search of the publications listed under the PubMed ‘cited by’ tab was performed for all references selected in abstract screening, and manual searches were performed of the reference sections for all publications identified by the systematic review. Results 10 publications were identified describing a total of 29 subjects with a broad range of epilepsy disorders treated with closed-loop thalamic neurostimulation. The median age of subjects was 31 years old (range 10 to 65 years). Of the 29 subjects, 15 were stimulated in the anterior, 11 in the centromedian, and 3 subjects in the pulvinar nuclei. Excluding 5 subjects who were treated for 1 month or less, median time on stimulation was 19 months (range 2.4 to 54 months). Of these subjects, 17/24 of experienced greater than or equal to 50%, 11/24 of subjects at least 75%, and 9/24 at least 90% reduction in seizures. Although a minority of patients did not exhibit significant clinical improvement by follow-up, there was a general trend of increasing treatment efficacy with longer periods on closed-loop thalamic stimulation. Conclusions: The data supporting off-label closed-loop thalamic stimulation is limited to 29 adult and pediatric patients with TRE, many of whom experienced significant improvement in seizure duration and frequency. This encouraging progress must be verified in larger studies.